Radiation from a pulse-excited thin wire monopole. - Bantin, Colin C.
The physics of radiation is explored in the time domain by examining the behavior of a pulse-excited thin wire monopole antenna. The feed-point current, the charge and current densities along the wire, and the electric fields in the space around the monopole are first found in the frequency domain, using the method of moments and the wire surface boundary conditions. The Fourier transform is then used to find the time-domain behavior. The results support the notion that radiation comes from the feed point and the tip regions, and by direct calculation it is shown to be due to the integrated value of a distribution of the accelerated charge density. The behavior of the current at the feed point, and the charge and current densities along the monopole, are discussed in light of these results.
Keywords: Electromagnetic radiation; Radiation physics; Pulse excited antennas; Time domain antennas; Monopole antennas